Do Current Recommendations for Upper Instrumented Vertebra Predict Shoulder Imbalance? An Attempted Validation of Level Selection for Adolescent Idiopathic Scoliosis. Issue 3 (October 2015) - Bjerke, Benjamin T.; Cheung, Zoe B.; Shifflett, Grant D.; Iyer, Sravisht; Derman, Peter B.; Cunningham, Matthew E.
Background: Shoulder balance for adolescent idiopathic scoliosis (AIS) patients is associated with patient satisfaction and self-image. However, few validated systems exist for selecting the upper instrumented vertebra (UIV) post-surgical shoulder balance. Questions/Purposes: The purpose is to examine the existing UIV selection criteria and correlate with post-surgical shoulder balance in AIS patients. Methods: Patients who underwent spinal fusion at age 10–18 years for AIS over a 6-year period were reviewed. All patients with a minimum of 1-year radiographic follow-up were included. Imbalance was determined to be radiographic shoulder height |RSH| ≥ 15 mm at latest follow-up. Three UIV selection methods were considered: Lenke, Ilharreborde, and Trobisch. A recommended UIV was determined using each method from pre-surgical radiographs. The recommended UIV for each method was compared to the actual UIV instrumented for all three methods; concordance between these levels was defined as "Correct" UIV selection, and discordance was defined as "Incorrect" selection. Results: One hundred seventy-one patients were included with 2.3 ± 1.1 year follow-up. For all methods, "Correct" UIV selection resulted in more shoulder imbalance than "Incorrect" UIV selection. Overall shoulder imbalance incidence was improved from 31.0% (53/171) to 15.2% (26/171). New shoulder imbalance incidence for patients with previously level shoulders was 8.8%. Conclusions: We could not identify a set of UIV selection criteria that accurately predicted post-surgical shoulder balance. Further validated measures are needed in this area. The complexity of proximal thoracic curve correction is underscored in a case example, where shoulder imbalance occurred despite "Correct" UIV selection by all methods.